Recycling flowback water for hydraulic fracturing in Sichuan Basin, China: Implications for gas production, water footprint, and water quality of regenerated flowback water. (15th July 2020) - Liu, Dan; Li, Jian; Zou, Caineng; Cui, Huiying; Ni, Yunyan; Liu, Jiaqi; Wu, Wei; Zhang, Lin; Coyte, Rachel; Kondash, Andrew; Vengosh, Avner
Graphical abstract: Highlights: Reuse flowback water for hydraulic fracturing reduces the blue water footprint of shale gas development. Reuse of flowback water for hydraulic fracturing could reduce the shale gas production. Hydraulic fracturing with saline water changes the water salinity and chemistry of flowback water. Tradeoff between reduction in fresh water utilization and shale gas productivity. Abstract: The increased water consumption for hydraulic fracturing and the volume of wastewater generated from shale gas and tight oil exploration are major environmental challenges associated with unconventional energy development. Recycling of the flowback and produced water for hydraulic fracturing is one of the solutions for reducing the water footprint of hydraulic fracturing and removing highly saline oil and gas wastewater. Here we investigated the implications of recycling saline wastewater for hydraulic fracturing by monitoring the natural gas production, flowback water volume, and the water quality of generated flowback water in shale gas wells from Changning gas field in Sichuan Basin, China. A comparison of two sets of shale gas wells, with six wells in each sub-group, from the same location in Changning gas field shows lower ( 20%) natural gas production and higher flowback water volume ( 18%) in wells that were fracked with recycled saline wastewater relative to wells that were fracked with fresh water after a year of production. Geochemical analysis suggests that hydraulic fracturing with saline wastewater increases the salinity of the wastewater and reduces the magnitude of water-shale rock interactions. In spite of the direct economic consequences in reduction in natural gas production from recycling of wastewater for hydraulic fracturing, in areas where water scarcity could become a limiting factor for future large-scale shale gas development, hydraulic fracturing with recycled flowback water can be more beneficial than utilization of limited freshwater resources, as long as the higher saline flowback water is fully recycled.